Edukasi Bijak Berswamedikasi Pada Siswa Sekolah Menengah Atas di Kecamatan Rajeg, Kabupaten Tangerang, Banten - arrahman, ikhsan nazar; Ul’Aufa, Rangga; Wulandari, Retno; Ayu, Restu; Musana, Rendika Hasanil; Sulis, Pretty Ananda (Jurnal Pengabdian Harapan Ibu (JPHI), 2025)
Self-medication is an effort to treat symptoms and/or minor illnesses, such as pain, fever, dizziness, cough, flu, diarrhea, constipation, or skin diseases. However, as time goes by, the level of abuse of self-medication drugs is increasing, especially among adolescents. This community service aims to improve the knowledge of high school students in Rajeg District, Tangerang Regency, Banten Province regarding self-medication activities. This community service is pre-experimental semi-quantitative with a pre-test & post-test study design. Sampling used the quota sampling technique with a sample size of 90 respondents. Before the intervention, 90% (n=81) of male respondents stated that they did not or did not understand much and 10% (n=9) of female respondents stated that they did not understand or did not understand enough regarding self-medication practices. After the intervention, there was an increase in the understanding of respondents. As many as 17.8% (n=16) of male respondents stated that they still did not understand self-medication, in female respondents the increase in understanding with the highest percentage was understanding 37.8% (n=34). The conclusion, education of wise self-medication can increase students' knowledge in self-medication activities.